2005
DOI: 10.1111/j.1478-3231.2005.01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the transforming growth factor‐β1 gene (TGF‐β1) and the risk of advanced alcoholic liver disease

Abstract: The polymorphisms at the TGF-beta(1) gene analysed in this study are probably not related to the risk of advanced ALD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
2
13
1
1
Order By: Relevance
“…This implies that the genetic polymorphism at codon 10 does not exert great effects on the development of ALC as a host factor. In the study reported by Oliver et al9 and Bathgate et al29 the development of ALC was not associated with the genetic polymorphism at the codon 10, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This implies that the genetic polymorphism at codon 10 does not exert great effects on the development of ALC as a host factor. In the study reported by Oliver et al9 and Bathgate et al29 the development of ALC was not associated with the genetic polymorphism at the codon 10, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, contradictory to this, it has been also reported that in the P/P genotype, the serum concentration of TGF-β1 is higher than other genotypes,23-26 and liver fibrosis progresses rapidly in the genotype containing proline 13,26. On the other hand, it has been also reported that the genotype at codon 10 is not associated with liver fibrosis 9,12,27,28. It is thought that the reason of such results contradictory to each other may be the effect of the sample size, races, and the difference of the cause of liver diseases such as HBV, hepatitis C virus (HCV), and alcohol.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast to hepatitis B infection, iron deposits are found in more than 50% of patients with HCV infection or chronic ethanol consumption [96,[106][107][108][109] . Even mild to moderate alcohol consumption has recently been shown to increase the prevalence of iron overload [110] .…”
Section: Ethanol and Hcv Lead To Hepatic Iron Accumulationmentioning
confidence: 99%
“…With regard to ALD, two studies have failed to find any association between ALD and the codon 25 Arg/Pro SNP in the TGF-b1 gene. 90,91 The only relevant study thus far in this regard in NAFLD reported that obese patients possessing both the high TGF-b1 and angiotensinogen-producing SNPs may be more susceptible to advanced fibrosis. 92 However interpretation of this study is limited by small numbers.…”
Section: Genes Influencing the Severity Of Fibrosismentioning
confidence: 97%